Developing a Short Form of the Self-Assessment Practices Scale: Psychometric Evidence - Yan, Zi (Frontiers in Education, 2020)
This research aimed to develop a short form of the Self-assessment Practices Scale (SaPS). Guided by a process model of self-assessment, the SaPS scale was designed to assess the actions students engage in during the self-assessment process. The data used for developing the original 20-item SaPS (SaPS-20), i.e., 1416 Hong Kong students ranging from Primary 4 to Secondary 3, were reanalyzed, and a 12-item short form (SaPS-SF) was developed. Factor analysis and Rasch analysis were applied in complementary ways to examine the psychometric properties of the SaPS-SF. The results showed that factor structure of the original scale held in the SaPS-SF, and all items fitted the Rasch model requirements sufficiently and measured the constructs as theorized. The findings presented in this study facilitate the measurement of self-assessment practice in a parsimonious and effective way.